A Practical Approach to Identifying Pediatric Disease-Associated Undernutrition: A Position Statement from the ESPGHAN Special Interest Group on Clinical Malnutrition. Issue 5 (3rd May 2022) - Hulst, Jessie M.; Huysentruyt, Koen; Gerasimidis, Konstantinos; Shamir, Raanan; Koletzko, Berthold; Chourdakis, Michail; Fewtrell, Mary; Joosten, Koen F.
Abstract : ABSTRACT: Disease-associated undernutrition (DAU) is still common in hospitalized children and is generally accepted to be associated with adverse effects on disease outcomes; hence making proper identification and assessment essential in the management of the sick child. There are however several barriers to routine screening, assessment, and treatment of sick children with poor nutritional status or DAU, including limited resources, lack of nutritional awareness, and lack of agreed nutrition policies. We recommend all pediatric facilities to 1) implement procedures for identification of children with (risk of) DAU, including nutritional screening, criteria for further assessment to establish diagnosis of DAU, and follow-up, 2) assess weight and height in all children asa minimum, and 3) have the opportunity for children at risk to be assessed by a hospital dietitian. An updated descriptive definition of pediatric DAU is proposed as "Undernutrition is a condition resulting from imbalanced nutrition or abnormal utilization of nutrients which causes clinically meaningful adverse effects on tissue function and/or body size/composition with subsequent impact on health outcomes." To facilitate comparison of undernutrition data, it is advised that in addition to commonly used criteria for undernutrition such as z score < −2 for weight-for-age, weight-for-length, or body mass index <−2, an unintentional decline of >1inthese z scores over time should be considered as an indicator requiring further assessment to establish DAU diagnosis. Since the etiology of DAU is multifactorial, clinical evaluation and anthropometry should ideally be complemented by measurements of body composition, assessment of nutritional intake, requirements, and losses, and considering disease specific factors.